Employment in the Canadian Medical Profession by Immigrant Status, Racialized Group and Gender - Christoph Schimmele and Feng Hou (Healthcare Policy, 2025)
This study examines how immigrant status and place of education affect skill utilization among Canadians with a medical degree, using the 2021 Census of Population. Immigrants with a foreign education were less likely to be employed as doctors than Canadian-educated immigrants or Canadian-born people. Among foreign-educated immigrants, racialized people had a larger disadvantage in employment as doctors than their White counterparts. Canadian-educated immigrants mostly had similar employment outcomes as Canadian-born people, but those from the Black, South Asian and Arab/West Asian groups had worse outcomes. A similar disadvantage was found among Canadian-born people from the Black, South Asian and Arab/West Asian groups.
Keywords: Canada; Foreign Medical Graduates; Healthcare Sector; Health Personnel; Health Resources; Immigrants; Medical Education